Contrast‐enhanced sonography for screening of vascular complication in recipients following living donor liver transplantation. Issue 5 (28th March 2013) - Lee, So Jung; Kim, Kyoung Won; Kim, So Yeon; Park, Yang Shin; Lee, Jeongjin; Kim, Hyoung Jung; Lee, Jong Seok; Song, Gi Won; Hwang, Shin; Lee, Sung‐Gyu
ABSTRACT The purpose of this article is to discuss the role of CEUS for screening of vascular complication in recipients admitted to ICU following LDLT, effect of microbubble contrast agent on Doppler phenomenon, CEUS technique, and illustrate CEUS findings in recipients with complication following LDLT. CEUS can enhance the role of US in the diagnosis of postoperative vascular complication in recipients following living donor liver transplantation at the bedside. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound, 41:305–312, 2013